Method for solubilizing water-absorbing resin, and method for producing water-absorbing resin

A solubilization process for water-absorbing resins, involving particle size reduction and controlled heating with minimal decomposing agents, addresses the inefficiencies of conventional methods by achieving rapid solubilization with preserved resin quality and reduced costs, suitable for recycling in water-absorbing resin production.

JP2025010894APending Publication Date: 2025-01-23NIPPON SHOKUBAI CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023113188
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-23

AI Technical Summary

Technical Problem

Conventional methods for solubilizing water-absorbing resins require a long time and use excessive amounts of decomposing agents, leading to increased costs and deterioration of resin properties.

Method used

A method involving a solubilization process that reduces the particle size of water-absorbing resins to 20-160 μm, uses a minimal amount of decomposing agent (0.001 to 1 part by mass per 100 parts by mass of resin), and includes heating at 50-130°C to achieve solubilization in a short time, while maintaining resin quality.

Benefits of technology

The method allows for rapid solubilization of water-absorbing resins without excessive decomposing agents, preserving resin properties and reducing production costs, enabling the use of solubilized polymers as raw materials for producing high-quality water-absorbing resins.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010894000001
    Figure 2025010894000001
  • Figure 2025010894000002
    Figure 2025010894000002
Patent Text Reader

Abstract

To provide a method for solubilizing a water-absorbing resin which can decompose a water-absorbing resin in a short time without using a large amount of decomposers.SOLUTION: A method for solubilizing a water-absorbing resin includes: a solubilization step of solubilizing a water-absorbing resin recovered from a used water-absorbing article or the like; and a particle diameter reduction step of crushing the water-absorbing resin so as to have a specific particle diameter and / or particle ratio.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for solubilizing a water-absorbent resin and a method for producing a water-absorbent resin. [Background technology]

[0002] In recent years, absorbent resins have been widely used as water absorbents in absorbent articles such as paper diapers, sanitary napkins, and incontinence pads, from the viewpoint of absorbing body fluids. Examples of such absorbent resins include hydrolyzates of starch-acrylonitrile graft copolymers, neutralized products of starch-acrylic acid graft polymers, saponified products of vinyl acetate-acrylic acid ester copolymers, and crosslinked products of partially neutralized acrylic acid polymers. From the viewpoint of water absorption performance, polyacrylic acid (salt)-based absorbent resins using acrylic acid and / or its salt as a monomer are most widely produced industrially.

[0003] Although absorbent articles are generally disposable, interest in recycling sanitary materials is growing due to growing environmental awareness. As a technology for recycling water-absorbent resins used in absorbent articles, a method has been developed in which the water-absorbent resins are decomposed, solubilized, and separated from other components in the paper diaper, and then the solubilized polymer is added to the manufacturing process of the water-absorbent resin for reuse (Patent Document 1).

[0004] As techniques for decomposing and solubilizing a water-absorbent resin, there have been developed a technique for solubilizing a water-absorbent resin by heat-treating a mixture of the water-absorbent resin and pulp in the presence of a decomposing agent such as hydrogen peroxide (Patent Document 2), a technique for solubilizing a water-absorbent resin by using ascorbic acid, which is a reducing agent, under conditions of pH 4 to 7.5 (Patent Document 3), a technique for solubilizing a water-absorbent resin by using a reducing agent and a transition metal ion (Patent Document 4), and a technique for solubilizing a water-absorbent resin by heating in the presence of an oxidative water-soluble salt (Patent Documents 5 to 7). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO2020 / 213298 [Patent Document 2] Patent Publication No. 04-317785 [Patent Document 3] Patent Publication No. 05-247221 [Patent Document 4] Patent Publication 2019-131789 [Patent Document 5] WO2021 / 042113 [Patent Document 6] WO2022 / 183184 [Patent Document 7] Special table 2022-544666 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the above-mentioned conventional techniques for solubilizing a water-absorbent resin require a long time to solubilize the water-absorbent resin, and thus have a problem from an economical point of view.

[0007] A method of using a large amount of a decomposition agent has been proposed as a method for shortening the time required for solubilization of a water-absorbent resin, but this method has problems such as an increase in the cost of the decomposition agent and a decrease in the physical properties (e.g., colorability) of the solubilized polymer and the water-absorbent resin made from the solubilized polymer.

[0008] In the above-mentioned circumstances, one aspect of the present invention is to provide a method for solubilizing a water-absorbent resin, which can solubilize a water-absorbent resin in a short time without using a large amount of a decomposition agent, and a method for producing a water-absorbent resin using a solubilized polymer obtained by the solubilization method as a part of a raw material. [Means for solving the problem]

[0009] In order to solve the above problems, one embodiment of the present invention includes the following configuration. [1] A method for solubilizing a water-absorbent resin, comprising: a solubilization step of solubilizing a water-absorbent resin recovered from used absorbent articles or waste generated in the manufacturing process of a water-absorbent resin to obtain a solubilized polymer; and a particle size reduction step of pulverizing the water-absorbent resin so that the mass average particle size, calculated as a dry matter, is 20 to 160 μm and / or so that the mass ratio of a particle fraction having a particle size of 80 μm or less, calculated as a dry matter, is 40 mass% or more. [2] The method for solubilizing a water-absorbent resin according to [1], wherein a decomposing agent is added to the water-absorbent resin in the solubilization step. [3] The method for solubilizing a water-absorbent resin according to [2], wherein the amount of the decomposition agent added is 0.001 to 1 part by mass with respect to 100 parts by mass of the water-absorbent resin. [4] The method for solubilizing a water-absorbent resin according to [2] or [3], wherein the decomposition agent is an oxidizing agent. [5] The method for solubilizing a water-absorbent resin according to any one of [1] to [4], wherein in the solubilization step, the water-absorbent resin is heated to 50 to 130°C. [6] The method for solubilizing a water-absorbent resin according to any one of [1] to [5], wherein the particle size reduction step is carried out before the solubilization step or simultaneously with the solubilization step. [7] The method for solubilizing a water-absorbent resin according to any one of [1] to [6], wherein in the particle size reduction step, the water-absorbent resin in a dry state is reduced in particle size. [8] The method for solubilizing a water-absorbent resin according to any one of [1] to [7], wherein the solubilizing polymer has a mass average molecular weight of 100,000 to 450,000. [9] The method for solubilizing a water-absorbent resin according to any one of [1] to [8], wherein the solubilized polymer has a YI value of 10.0 or less.

[10] The method for solubilizing a water-absorbent resin according to any one of [1] to [9], wherein the solubilized polymer has a solid content concentration of 1 to 90 mass %.

[11] The method for solubilizing a water-absorbent resin according to any one of [1] to

[10] , wherein the water-absorbent resin is a water-absorbent resin recovered from a used absorbent article.

[12] A method for producing a water-absorbent resin, comprising using a solubilized polymer obtained by the method for solubilizing a water-absorbent resin according to any one of [1] to

[11] as a part of a raw material in a production process of the water-absorbent resin using a monomer constituting the water-absorbent resin as a raw material.

[13] A method for producing a water absorbent resin according to

[12] , comprising a step of preparing an aqueous monomer solution, a polymerization step, an optional gel crushing step, a drying step, an optional crushing step after drying, a classification step, and a surface crosslinking step, and the solubilizing polymer is added before the drying step. Effect of the Invention

[0010] According to one aspect of the present invention, it is possible to provide a method for solubilizing a water-absorbent resin, which can solubilize a water-absorbent resin in a short time without using a large amount of a decomposition agent, and a method for producing a water-absorbent resin using a solubilized polymer obtained by the solubilization method as a part of a raw material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited to this, and various modifications are possible within the scope described, and the technical scope of the present invention also includes embodiments obtained by appropriately combining the technical means disclosed in different embodiments. In this specification, unless otherwise specified, "A to B" representing a numerical range means "A or more, B or less." In addition, "acid (salt)" means "acid and / or its salt," and "(meth)acrylic" means "acrylic and / or methacrylic."

[0012] [1] Method for solubilizing water-absorbent resin In one embodiment of the present invention, a method for solubilizing a water-absorbent resin is provided, comprising a solubilization step of solubilizing a water-absorbent resin recovered from used absorbent articles or waste generated in the manufacturing process of the water-absorbent resin to obtain a solubilized polymer, and a particle size reduction step of pulverizing the water-absorbent resin so that the mass average particle size calculated as a dry matter is 20 to 160 μm and / or the mass ratio of a particle fraction having a particle size of 80 μm or less calculated as a dry matter is 40 mass% or more. According to the method for solubilizing an absorbent resin according to one embodiment of the present invention (hereinafter, sometimes referred to as "the solubilization method"), the water-absorbent resin can be solubilized in a relatively short time without using a large amount of a decomposing agent (or without using a decomposing agent itself).

[0013] (1-1) Water-absorbing resin In the present specification, the term "water-absorbent resin" refers to a water-swellable, water-insoluble polymer gelling agent, and generally means a commonly used water-absorbent resin having a water absorption capacity of 10 to 1000 times its volume. More specifically, it is preferable that the water-absorbent resin before absorbing the liquid to be absorbed satisfies the physical property of a CRC of 5 g / g or more as "water-swellability" as specified in ERT441.2-02, and satisfies the physical property of an Ext (water-soluble content) of 0 to 50 mass% as "water-swellability" as specified in ERT470.2-02.

[0014] Specific examples of water-absorbent resins include polyacrylic acid (salt)-based resins, polysulfonic acid (salt)-based resins, maleic anhydride (salt)-based resins, polyacrylamide-based resins, polyvinyl alcohol-based resins, polyethylene oxide-based resins, polyaspartic acid (salt)-based resins, polyglutamic acid (salt)-based resins, polyalginic acid (salt)-based resins, starch-based resins, cellulose-based resins, (meth)acrylate crosslinked polymers, saponified crosslinked products of (meth)acrylate-vinyl acetate copolymers, starch-acrylate graft polymers and crosslinked products thereof.

[0015] The "water-absorbent resin" in this specification is not limited to an embodiment in which the total amount (100 mass%) is only the above-mentioned water-absorbent resin (for example, a polyacrylic acid (salt)-based resin), and may be in the form of a water-absorbent resin composition further containing additives and the like.

[0016] The mass of the "water-absorbent resin" in this specification is a value converted into solid content unless otherwise specified. When the mass of the water-absorbent resin contained in a used absorbent article is unknown, the mass of the water-absorbent resin contained in an unused absorbent article of the same type and the general value of the water absorption capacity of the water-absorbent resin in the used absorbent article can be used, or the content of the water-absorbent resin (solid content equivalent value) relative to the total mass of the used absorbent article can be assumed to be 3 to 9 mass%, thereby measuring the mass of the water-absorbent resin contained in the used absorbent article. Detailed measurement conditions can be appropriately adjusted by a person skilled in the art according to the actual situation of the absorbent article, etc.

[0017] (1-3) Absorbent articles In this specification, the term "absorbent article" refers to an article used for water absorption. An example of the "absorbent article" is an absorbent article comprising an absorbent body containing a water-absorbing resin and a fibrous material, a top sheet having liquid permeability, and a back sheet having liquid impermeability. The absorbent body is suitably manufactured by blending the water-absorbing resin with a fibrous material, or by sandwiching the water-absorbing resin between fibrous materials and molding the mixture into a film, a tube, a sheet, or other shape. Here, examples of the fibrous material include hydrophilic fibers such as crushed wood pulp, cotton linters, crosslinked cellulose fibers, rayon, cotton, wool, acetate, vinylon, and the like. Specific examples of the "absorbent article" include sanitary materials (sanitary products) such as paper diapers, sanitary napkins, adult incontinence products (incontinence pads), and pet sheets, but are not limited thereto.

[0018] The term "used absorbent article" in this solubilization method refers to an absorbent article (particularly, a sanitary material) that has absorbed any liquid (liquid to be absorbed), particularly bodily fluids such as urine and blood.

[0019] (1-4) Waste generated during the manufacturing process of water-absorbent resin In this specification, the term "waste generated during the manufacturing process of a water-absorbent resin" refers to a water-absorbent resin that is generated during the manufacturing process of a water-absorbent resin and is rejected from product use for some reason (for example, because its water-absorbing properties, color tone, etc. are not within the standard), and is usually discarded, and is therefore referred to as "waste." Examples of "waste generated during the manufacturing process of a water-absorbent resin" include, but are not limited to, fine powder, gel, and water-absorbent resin particles with excessively large or small particle diameters generated during the manufacturing process of a water-absorbent resin.

[0020] (1-5) Solubilization process The present solubilization method includes a solubilization step of solubilizing a water-absorbent resin recovered from used absorbent articles or waste generated in the manufacturing process of a water-absorbent resin (hereinafter, such a water-absorbent resin recovered from used absorbent articles or waste generated in the manufacturing process of a water-absorbent resin, in other words, a water-absorbent resin to be recycled, may be referred to as a "recovered water-absorbent resin").

[0021] The solubilization step can be said to be a step of solubilizing the recovered water absorbent resin, which is usually water-swellable (i.e., insoluble in water), in water to obtain a water-soluble polymer (solubilized polymer). The solubilized polymer obtained in the solubilization step may be one in which the entire amount of the recovered water absorbent resin as the raw material is solubilized in water, or may be a partially solubilized product containing a polymer that is not partially solubilized. In the solubilization step, it is preferable that 50% by mass or more of the recovered water absorbent resin is solubilized, more preferably 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more is solubilized, and it is particularly preferable that substantially 100% by mass is solubilized.

[0022] The method for solubilizing the recovered water-absorbent resin is not particularly limited as long as it is a method that can decompose the water-absorbent resin and solubilize it in water, and examples thereof include a method for solubilizing the water-absorbent resin using a decomposing agent (e.g., an oxidizing agent); a method for solubilizing the water-absorbent resin by heating; and a method for solubilizing the water-absorbent resin by light irradiation. Among these, in the present solubilization method, it is preferable to solubilize the recovered water-absorbent resin using a decomposing agent, and it is further preferable to use heating in combination, since this method is excellent in decomposition efficiency (time and energy) and molecular weight control after decomposition. In addition, two or more of these methods may be combined to perform solubilization.

[0023] In the present solubilization method, when the water absorbent resin is solubilized using a decomposing agent, the method of contacting the recovered water absorbent resin with the decomposing agent includes a method of adding the decomposing agent (aqueous solution containing the decomposing agent) to a gel (swollen gel) of the recovered water absorbent resin in a pre-swollen state, a method of adding the decomposing agent (aqueous solution containing the decomposing agent) to the recovered water absorbent resin in a dry state, etc. Among these, the method of adding the decomposing agent (aqueous solution containing the decomposing agent) to the recovered water absorbent resin in a dry state is preferred, since the decomposing agent can be mixed uniformly into the recovered water absorbent resin.

[0024] In addition, the term "(recovered) water absorbent resin in a dry state" in this specification is a concept including a completely dry water absorbent resin (water content is 0 parts by mass relative to 100 parts by mass of water absorbent resin) as well as a substantially dry water absorbent resin in which the water content is 30 parts by mass or less relative to 100 parts by mass of water absorbent resin.

[0025] (1-6) Decomposition agent In the solubilization step, the decomposition agent that can be used is not particularly limited as long as it can decompose (solubilize) the water-absorbent resin to obtain a solubilized polymer, and examples thereof include oxidizing agents, reducing agents, transition metal ions, heavy metals, etc. In addition, when decomposition is performed by light energy (particularly ultraviolet light), a sensitizer such as benzophenone may be used as the decomposition agent. Each of these decomposition agents may be used alone or in combination of two or more.

[0026] When a decomposing agent is used in the present solubilization method, the amount of the decomposing agent used (addition amount) is preferably 0.001 to 1 part by mass relative to 100 parts by mass of the recovered water absorbent resin (solid content equivalent), and more preferably 0.01 to 0.5 parts by mass. Since the present solubilization method includes a particle size reduction step, even if the amount of the decomposing agent used is relatively small (compared to conventional methods) of 0.001 to 1 part by mass, the recovered water absorbent resin can be sufficiently solubilized in a relatively short time. In addition, when the amount of the decomposing agent used is large (for example, more than 1 part by mass, particularly 2 parts by mass or more relative to 100 parts by mass of the recovered water absorbent resin), the decomposing agent remains in the solubilized polymer, which may cause a hindrance to the next step, or the solubilized polymer may change due to the influence of the remaining decomposing agent, causing the resulting solubilized polymer to be colored. However, the present solubilization method can solubilize the recovered water absorbent resin with a relatively small amount of decomposing agent as described above, and therefore can also suppress coloring of the resulting solubilized polymer.

[0027] (1-6-1) Oxidizing agent In the present specification, the term "oxidizing agent" refers to a compound having oxidizing properties, which generates radicals under certain conditions. Examples of the oxidizing agent include peroxides such as hydrogen peroxide, alkyl hydroperoxides, and peresters; perchlorates such as sodium perchlorate and potassium perchlorate; periodates such as sodium periodate and potassium periodate; percarbonates, perborates, and peracetic acid. Among them, hydrogen peroxide is preferred as the oxidizing agent used in the present solubilization method, because of its excellent decomposition efficiency and molecular weight control.

[0028] (1-6-2) Reducing agent In the present specification, the term "reducing agent" refers to a compound having reducing properties, which generates radicals under certain conditions. Examples of reducing agents include oxidizing agents such as peroxides such as hydrogen peroxide, alkyl hydroperoxides, and peresters, perchloric acid (salts), periodic acid (salts), percarbonic acid (salts), perboric acid (salts), and peracetic acid; sulfurous acid (salts), hydrogen sulfite (salts), phosphorous acid (salts), hypophosphorous acid (salts), thiosulfuric acid (salts), formic acid, oxalic acid, erythorbic acid, amines, ascorbic acid (salts) or derivatives thereof (e.g., L-ascorbic acid (salts), isoascorbic acid (salts), and alkyl esters of ascorbic acid), phosphate esters, and sulfate esters. Among these, sulfurous acid (salts), hydrogen sulfite (salts), L-ascorbic acid (salts), and isoascorbic acid (salts) are preferred as reducing agents used in the present solubilization method, due to their excellent decomposition efficiency and safety.

[0029] (1-6-3) Transition metal ions Transition metal ions that can be used as decomposition agents in the present solubilization method include, for example, Cu 2+ , Ag + , Fe 2+ , Fe 3+ , Al 3+ , Ni 2+ , Mn 2+ Among them, iron ions (Fe ) are the most popular because of their high decomposability. 2+ ) or copper ions (Cu 2+ ) is preferred, and iron ions (Fe 2+ ) is more preferable. The transition metal ion can also be used in the form of a compound that generates the transition metal ion. Examples of such compounds that generate transition metal ions include chlorides and hydrates thereof, such as ferrous chloride, organic acid salts and hydrates thereof, such as ferrous fumarate, ferrous oxalate, ferrous chloride, sodium ferrous citrate, ferrous gluconate, ferrous citrate, ferrous acetate, sulfates and hydrates thereof, such as ferrous sulfate, and the like.

[0030] (1-6-4) Acid or alkali In the present solubilization method, the recovered water absorbent resin, particularly the crosslinking points of the recovered water absorbent resin, may be hydrolyzed by an acid or an alkali. As the acid or alkali that can be used in the present solubilization method, a known acid or alkali that is used in normal hydrolysis may be used, but in terms of hydrolysis efficiency, a strong acid or strong alkali, particularly a strong alkali (hydroxide of an alkali metal, for example, KOH or NaOH), is preferably used. These acids or alkalis may be added to the recovered water absorbent resin simultaneously with the decomposing agent (i.e., in the solubilization step), or may be added at any other timing.

[0031] (1-6-5)pH When the recovered water absorbent resin is solubilized using a decomposer in the present solubilization method, a wide range of pH from strongly acidic to strongly alkaline can be applied, and for example, a range of pH=1 to 14 or 2 to 12 can be selected. Among them, from the viewpoint of decomposition efficiency, it is preferable to solubilize the recovered water absorbent resin in a state in which the pH of the mixture obtained by adding the decomposer to the recovered water absorbent resin is adjusted to a range of 6.5 to 8.5, more preferably to pH 6.5 to 8.3, and even more preferably to pH 6.5 to 8.0. By performing the solubilization treatment in a state in which the pH is controlled within the above range, the recovered water absorbent resin can be sufficiently solubilized (decomposed) in a shorter time while suppressing coloration. The pH of the mixture may be adjusted within the above range at least for a certain period of time (for example, about 1 hour) that allows the decomposition of the recovered water absorbent resin to proceed sufficiently, but it is preferable to adjust the pH to be within the above range from the start of decomposition to the end of decomposition.

[0032] The pH of the mixture can be adjusted by further adding a pH adjuster such as an acid or a base. Examples of acids that can be used as pH adjusters include inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid, and organic acids such as acetic acid and citric acid. Examples of bases that can be used as pH adjusters include sodium hydroxide, sodium carbonate, potassium hydroxide, and magnesium hydroxide.

[0033] (1-7) Solubilization temperature In the present solubilization method, the temperature at which the recovered water absorbent resin is solubilized (solubilization temperature), and when a decomposing agent is used, the temperature of the mixture obtained by adding the decomposing agent to the recovered water absorbent resin, are not particularly limited, but are preferably 50 to 130°C, more preferably 65 to 120°C, and even more preferably 80 to 110°C. By controlling the solubilization temperature within the above range, the recovered water absorbent resin can be solubilized more efficiently, and as a result, a solubilized polymer having better physical properties can be provided in a shorter time. The method of adjusting the solubilization temperature is not particularly limited, and examples thereof include a method of immersing a container filled with the recovered water absorbent resin or the like in an oil bath at a predetermined temperature, a method of subjecting the recovered water absorbent resin, which has been heated to a predetermined temperature in advance, to a solubilization treatment, and maintaining the temperature during the solubilization treatment, and the like.

[0034] (1-8) Other solubilization methods As a specific embodiment of the solubilization step in the present solubilization method, a known method for solubilizing a water-absorbent resin can also be adopted. Examples of the method for solubilizing a water-absorbent resin include a method for decomposing and solubilizing a water-absorbent resin with a reducing agent and a transition metal ion (for example, the method described in JP 2019-131789 A), a method for solubilizing a water-absorbent resin using ascorbic acid as a reducing agent under conditions of pH 4 to 7.5 (for example, the method described in JP 3146053 A), and a method for solubilizing a water-absorbent resin by heat treatment in the presence of an oxidizing agent (for example, JP 3091251 A and JP 2022-5 44666), a method of using an oxidizing agent and a shear force in combination (for example, a method described in WO2022 / 183184, etc.), a method of solubilizing a water absorbent resin using chlorine dioxide under acidic conditions (for example, a method described in JP2019-108639A), a method of solubilizing a water absorbent resin using hydrogen peroxide (for example, a method described in JP2019-108640A), a method of solubilizing a water absorbent resin with ozone water containing ozone (for example, a method described in JP2019-085343A, etc. described in JP-A-6-213008); a method of solubilizing a water absorbent resin using a transition metal ion and a reducing agent (for example, the method described in JP-A-2019-131789); a method of decomposing a water absorbent resin by mechanical action and / or chemical action that can break chemical bonds (for example, the method described in WO2020 / 213298), a method of solubilizing a water absorbent resin by irradiating with electromagnetic waves (for example, microwaves) (for example, the method described in JP-A-2023-038963, US2021 / 0054164); a method of solubilizing a water absorbent resin by irradiating with ultraviolet irradiation (for example, the method described in US2021 / 0053028); a method of solubilizing a water absorbent resin by irradiating with ultrasonic waves (for example, the method described in US2021 / 0054161), a method of using an alkali or acid or even an oxidizing agent (for example, the method described in JP-A-9-249711), etc.

[0035] (1-9) Particle size reduction process This solubilization step includes a particle size reduction step of pulverizing the recovered water-absorbing resin so that the mass average particle size calculated as a dry product is 20 to 160 μm, and / or so that the mass ratio of the particle fraction having a particle size of 80 μm or less calculated as a dry product is 40 mass% or more. By reducing the particle size of the recovered water-absorbing aqueous resin in the particle size reduction step, the surface area of ​​the recovered water-absorbing aqueous resin is increased, and the solubilization treatment can be carried out efficiently. As a result, the time required for the solubilization treatment can be shortened while reducing (or not using) the amount of decomposing agent used.

[0036] The particle size reduction step can be preferably applied in a method for solubilizing a water-absorbent resin, particularly including a solubilization step using a decomposer (or an oxidizing agent). In this case, the particle size reduction step may be performed simultaneously with the solubilization of the water-absorbent resin by the decomposer in the solubilization step, or may be performed prior to the solubilization step, but preferably, the solubilization step is performed after the particle size reduction step. When the solubilization step is performed after the particle size reduction step, the decomposer may be added after the water-absorbent resin (powder or hydrous gel of the water-absorbent resin, particularly the water-absorbent resin powder) is reduced in particle size to the above range, or the water-absorbent resin (particularly the hydrous gel of the water-absorbent resin) in a state containing the decomposer may be reduced in particle size to the above range.

[0037] In the particle size reduction step, the primary particles or secondary particles (aggregates or granules of primary particles) of the recovered water absorbent resin may be reduced in particle size within the above range, and the recovered water absorbent resin may be reduced in particle size by any of the following means: pulverization of primary particles, destruction of agglomerations or granulations of secondary particles, or pulverization of primary particles and destruction of secondary particles into primary particles. By reducing the particle size of the recovered water absorbent resin in this way, the penetration of the decomposing agent into the recovered water absorbent resin particles and the penetration of heat and light having a decomposing effect into the recovered water absorbent resin particles are promoted. In addition, the molecular weight of the solubilized polymer after decomposition tends to be uniform. On the other hand, if the recovered water absorbent resin is not reduced in particle size, a difference occurs between the decomposability of the inside and the surface of the recovered water absorbent resin particles, and excessive time and decomposing agent are required for decomposition to the inside of the recovered water absorbent resin. As a result, not only is a long decomposition time and an excessive decomposing agent required, but there is also a risk of problems with the molecular weight and coloring of the obtained solubilized polymer, which is not preferable.

[0038] In the particle size reduction step, the recovered water absorbent resin is reduced in particle size so as to satisfy at least one of the following: "the mass average particle size (Solid D50) when converted into a dry matter is 20 to 160 μm" and "the mass ratio of the particle fraction having a particle size of 80 μm or less when converted into a dry matter is 40 mass% or more."

[0039] The mass average particle size (Solid D50) of the recovered water absorbent resin after the particle size reduction is preferably 20 to 160 μm when calculated as a dry product, and is more preferably 30 to 120 μm, and even more preferably 40 to 80 μm, in consideration of the balance between the energy and time required for the particle size reduction and the effect of the particle size reduction. The mass ratio of the particle fraction having a particle size of 80 μm or less when calculated as a dry product of the recovered water absorbent resin after the particle size reduction is preferably 40 mass% or more, more preferably 50 mass% or more, and even more preferably 60 mass% or more. The upper limit of the mass ratio of the particle fraction having a particle size of 80 μm or less when calculated as a dry product is not particularly limited, but may be, for example, 90 mass% or less, in consideration of the balance between the energy and time required for the particle size reduction and the effect of the particle size reduction.

[0040] The mass average particle size (Solid D50) of the recovered water absorbent resin before the particle size reduction is not particularly limited and can be appropriately selected, but is usually more than 160 μm, further 200 to 800 μm, particularly 250 to 700 μm, or 300 to 600 μm. The mass ratio of the particle fraction having a size of more than 160 μm is preferably 50% by mass or more, further 60% by mass or more, or 70% by mass or more.

[0041] Further, from the viewpoint of more efficient and uniform solubilization of the recovered water absorbent resin, in the particle size reduction step, the mass average particle diameter of the recovered water absorbent resin before the particle size reduction, converted into a dried product, is preferably reduced by 10% or more (i.e., the mass average particle diameter of the recovered water absorbent resin after the particle size reduction, converted into a dried product, is 9 / 10 or less of that before the particle size reduction), and is preferably reduced by 20% or more, 50% or more (1 / 2 or less), 75% or more (1 / 4 or less), or 80% or more (1 / 5 or less). Note that, when the particle size reduction step is performed on the powder of the recovered water absorbent resin, the mass average particle diameter of the recovered water absorbent resin converted into a dried product may be calculated from the mass average particle diameter of the swollen gel of the recovered water absorbent resin, and the mass average particle diameter or particle size distribution of the recovered water absorbent resin converted into a dried product may be calculated from the mass average particle diameter of the swollen gel, but since the particle diameter of the swollen gel converted into a dried product is almost the same as the particle diameter of the water absorbent resin powder before swelling, it may be substituted by measuring the particle diameter of the water absorbent resin powder.

[0042] The "mass average particle size (Solid D50) when converted into a dry matter" and the "mass ratio of the particle fraction having a particle size of 80 μm or less when converted into a dry matter" of the recovered water absorbent resin (after the particle size reduction) can be measured by the method described in the Examples.

[0043] In the particle size reduction step, the method of reducing the particle size of the recovered water absorbent resin is not particularly limited, but for example, a method of applying a shear force to the water absorbent resin to disintegrate it can be mentioned. In addition, either the recovered water absorbent resin in a dry state or the recovered water absorbent resin in a wet state may be reduced in particle size. The disintegration device when applying a shear force to the water absorbent resin to reduce the particle size is not particularly limited, but when the recovered water absorbent resin is in a dry state, a jaw crusher, a cone crusher, an impact crusher, a roll crusher, an autogenous crusher, a stamp mill, a stone mill, a crusher, a ring mill, a roller mill, a jet mill, a pin mill, a vibration mill, a planetary mill, a bead mill, an attritor, a hammer mill, a cutter mill, etc. can be used. Using these crushing devices, the primary particles or secondary particles of the recovered water absorbent resin can be reduced in particle size.

[0044] In addition, when the recovered water absorbent resin is in a hydrated state (gel-like), a gel crusher equipped with a plurality of rotating agitating blades, such as a batch or continuous twin-arm kneader, a single-screw extruder, a twin-screw extruder, a meat chopper, a disperser, a homomixer, a colloid mill, a roll mill, a high-pressure jet disperser, a rotary mill, a vibration mill, a planetary mill, an attritor, a bead mill, or the like can be used.

[0045] In particular, when the recovered water absorbent resin to be reduced in particle size is in a powder state, it is preferable to reduce the particle size of the recovered water absorbent resin in a dry state in the particle size reduction step, since this has the advantage of high pulverization efficiency. Also, when the recovered water absorbent resin to be reduced in particle size is a hydrogel, it may be dried to a powder state and then pulverized, or it may be pulverized in the hydrogel state. However, in consideration of the energy required for drying and the effort required to make a hydrogel (particularly a hydrogel containing a decomposing agent) after re-pulverization, it may be preferable to pulverize in the hydrogel state.

[0046] The particle size reduction step may be performed before the solubilization step, or may be performed simultaneously with the solubilization step. When the particle size reduction step is performed simultaneously with the solubilization step, for example, the particle size reduction treatment can be performed on the recovered water absorbent resin in a state in which a decomposition agent has been added. Since the recovered water absorbent resin can be efficiently solubilized, the particle size reduction step is preferably performed before the solubilization step.

[0047] (1-10) Mass average molecular weight of solubilizing polymer The mass average molecular weight of the solubilized polymer obtained by the present solubilization method is not particularly limited, but is preferably 10,000 to 1,000,000, more preferably 15,000 to 750,000, and even more preferably 20,000 to 500,000. Furthermore, from the viewpoint of using it as a raw material for a water-absorbent resin, it is preferably 100,000 to 450,000, more preferably 15,0000 to 40,000, and even more preferably 200,000 to 30,000. If the mass average molecular weight of the obtained solubilized polymer is within the above range, the handleability of the aqueous solution containing the solubilized polymer is improved, and further, in the water-absorbent resin produced using the solubilized polymer as a part of the raw material, the composite of the water-absorbent resin raw material and the solubilized polymer progresses efficiently, thereby reducing the amount of water-soluble content of the obtained water-absorbent resin and improving the water absorption properties.

[0048] In the present solubilization method, by carrying out a particle size reduction step in which the recovered water absorbent resin is reduced to a specific particle size, decomposition proceeds more uniformly in the interior and on the surface of the recovered water absorbent resin particles in the solubilization step. Therefore, it is easy to control the molecular weight of the obtained solubilized polymer, and it is possible to provide a solubilized polymer that is suitable not only for the purpose of decomposing and disposing the water absorbent resin, but also as a raw material for the water absorbent resin to be used in products.

[0049] (1-11) YI value of solubilizing polymer The YI value of the solubilized polymer obtained by the present solubilization method is preferably 10.0 or less, more preferably 5.0 or less, and even more preferably 4.0 or less. The lower limit of the YI value is not particularly limited, and may be, for example, 1.0 or more, or 0. The YI value of the solubilized polymer is an index indicating the colorability of the solubilized polymer, and the YI value of the solubilized polymer being within the above range means that the coloring of the water absorbent resin produced using the solubilized polymer as a part of the raw material is more suppressed. In the present solubilization method, the recovered water absorbent resin is reduced in particle size to a specific particle size, so that when the recovered water absorbent resin is solubilized, the decomposition proceeds more uniformly inside and on the surface of the recovered water absorbent resin particles. Therefore, excessive decomposition agents or long-term decomposition treatment are not required to solubilize the recovered water absorbent resin, and a solubilized polymer with little coloring is obtained that is suitable not only for the purpose of decomposing and disposing the water absorbent resin, but also as a raw material for the water absorbent resin for product use.

[0050] In this specification, the "YI value of a solubilized polymer" is a value measured by applying the method described in the Examples to an aqueous solution of a solubilized polymer having a solid content concentration of 8.00 to 10.00% by mass.

[0051] (1-12)Solubilized polymer solids concentration The solid content concentration of the solubilized polymer (aqueous solution) obtained by the present solubilization method is not particularly limited, but the solid content concentration of the solubilized polymer aqueous solution obtained is preferably 0.1% by mass or more, more preferably 1 to 90% by mass, and even more preferably 5 to 85% by mass, or 10 to 80% by mass. The solid content concentration of the solubilized polymer aqueous solution obtained can be appropriately adjusted by the concentration and heating in the decomposition step, and further by concentrating or diluting the solubilized polymer after the decomposition step as necessary. If the solid content concentration of the solubilized polymer (solubilized polymer aqueous solution) is within the above range, there is an advantage that it can be applied to a wide range of applications such as raw materials for water-absorbent resins or other solubilized polymer applications. In addition, an excessively dilute solution is restricted in the application and amount used (consumption) of the solubilized polymer, and is not preferable from the viewpoint of recycling the water-absorbent resin. On the other hand, if the concentration is excessively high, the viscosity of the solubilized polymer may be too high, resulting in poor handling. In this specification, the "solids concentration of the solubilizing polymer" is a value measured by the method described in the Examples.

[0052] (1-13) Other components of solubilizing polymers (Residual water absorbent resin) The solubilized polymer may be in the form of a dry product or an aqueous solution having a solid content concentration in the above range. In the present solubilization method, preferably 50% by mass or more, more preferably 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, particularly preferably substantially 100% by mass of the recovered water absorbent resin is solubilized, but the obtained solubilized polymer may contain a small amount of (undecomposed) water absorbent resin in addition to the above mass of solubilized polymer. That is, the solubilized polymer obtained by the present solubilization method may be a mixture of a solubilized polymer and an (undecomposed) water absorbent resin, containing 50% by mass or less, preferably 40% by mass or less, 30% by mass or less, 20% by mass or less, or 10% by mass or less of the (undecomposed) water absorbent resin in the total mass (100% by mass) including the (undecomposed) water absorbent resin.

[0053] (heavy metal ions and L-ascorbic acid) Heavy metal ions and L-ascorbic acid may cause coloring or deterioration of the water absorbent resin. Therefore, from the viewpoint of using them as raw materials for water absorbent resins for product applications, the amount of heavy metal ions and L-ascorbic acid in the solubilized polymer obtained by the present solubilization method is preferably as small as possible, and specifically, the amount is preferably 10 ppm or less, more preferably 5 ppm or less, 2 ppm or less, or 1 ppm or less, and particularly preferably ND (detection limit or less), relative to the solid content of the solubilized polymer. As for heavy metal ions and L-ascorbic acid, impurities derived from urine contained in used absorbent articles, or heavy metal ions and L-ascorbic acid used as decomposition agents (or used in the production of recovered water absorbent resin) may be contained in the solubilized polymer obtained by the present solubilization method, but the amount of heavy metal ions and L-ascorbic acid in the solubilized polymer can be controlled to the above range by purifying the recovered water absorbent resin, or by using heavy metal ions and L-ascorbic acid as decomposition agents in an amount not exceeding a certain amount.

[0054] (Residual decomposition agent) In the solubilization step, particularly when an oxidizing agent is used as a decomposing agent, the decomposing agent (oxidizing agent) may remain in the obtained solubilized polymer. From the viewpoint of using the solubilized polymer as a raw material for a water-absorbing resin (particularly for product use), the less the residual decomposing agent (residual oxidizing agent) in the solubilized polymer, the more preferable, specifically, it is preferably 100 ppm or less, 50 ppm or less, 20 ppm or less, or 10 ppm or less relative to the solid content of the solubilized polymer. In particular, the residual oxidizing agent may cause further changes in the performance or molecular weight of the solubilized polymer after decomposition, and may cause destabilization of polymerization when the solubilized polymer is used as a part of the raw material for the water-absorbing resin. Therefore, from the viewpoint of providing a more homogeneous water-absorbing resin, it is preferable that the amount of the residual oxidizing agent in the solubilized polymer is controlled to the above range. The amount of the residual decomposing agent (oxidizing agent) in the solubilized polymer can be controlled by a known method.

[0055] (1-14) Solubilized polymer manufacturing equipment The present solubilization method can also be carried out using an apparatus (manufacturing apparatus) capable of decomposing the recovered water absorbent resin while maintaining the desired decomposition conditions constant. Such an apparatus is not particularly limited, but includes a tank-type decomposition apparatus, a decomposition apparatus equipped with an agitator, a multi-shaft decomposition apparatus, and the like.

[0056] In order to reduce the frequency of equipment maintenance and maintain performance, the inner wall surface of the decomposition device is preferably made of a corrosion-resistant (acid-resistant, alkali-resistant) material. Examples of such corrosion-resistant materials include stainless steel, Hastelloy steel, titanium steel, glass-lined steel, resin-lined steel, and metal spray-coated steel. Examples of stainless steel include austenitic stainless steel such as SUS304, SUS304L, SUS304LN, SUS312L, SUS316, SUS316L, SUS316N, SUS316LN, SUS317, SUS317N, and SUS317LN; ferritic stainless steel such as SUS430, SUS430F, SUS434, and SUS444; and martensitic stainless steel such as SUS410, SUS410F2, SUS410J1, SUS410S, and SUS431. Resin-lined steel includes steel lined with rubber, fluororesin (polytetrafluoroethylene, perfluoroalkoxyalkane, perfluoroethylenepropylene copolymer, ethylenetetrafluoroethylene copolymer, polyvinylidene fluoride, etc.), and thermosetting resin (epoxy resin, bisphenol-type polyester, vinyl ester, etc.). Metal-sprayed coated steel includes steel coated with metal, ceramic, or a mixture thereof by flame spraying, high-velocity flame spraying, arc spraying, plasma spraying, or wire explosion spraying. The apparatus used in the present solubilization method may be one in which the lining or coating is applied to the entire apparatus, or only to the parts that are particularly susceptible to corrosion (such as the gas-liquid interface).

[0057] Other corrosion prevention measures besides the use of corrosion-resistant materials include regular washing of equipment with water, homogenizing the pH of the solution by thoroughly stirring or leaving it to stand before heating when adding acid or alkali, and removing oxygen from the solution (by replacing it with an inert gas, degassing it, using an oxygen scavenger, etc.).

[0058] [2] A method for producing a water-absorbent resin using a solubilized polymer obtained by decomposing a recovered water-absorbent resin as part of the raw material In one embodiment of the present invention, there is provided a method for producing a water-absorbent resin, in which a solubilized polymer obtained by the present solubilization method is used as a part of a raw material in a process for producing a water-absorbent resin from a monomer constituting the water-absorbent resin. Hereinafter, the "method for producing an absorbent resin according to one embodiment of the present invention" may be referred to as the "present production method".

[0059] According to the present production method, it is possible to provide a water-absorbent resin that is excellent in various physical properties (particularly colorability) while using recovered water-absorbent resin as a part of the raw material.

[0060] In the present production method, "production of a water-absorbent resin using a monomer constituting the water-absorbent resin as a raw material" refers to a normal method for producing a water-absorbent resin (without using a raw material derived from a recovered water-absorbent resin) using a monomer constituting the water-absorbent resin as a raw material, for example, a method for producing a water-absorbent resin (without using a raw material derived from a recovered water-absorbent resin) including a step of preparing an aqueous monomer solution, a polymerization step, an optional step of crushing a hydrogel, a step of drying a hydrogel, an optional step of crushing after drying, a classification step, and a surface crosslinking step. Therefore, one aspect of the present production method can also be expressed as a method for producing a water-absorbent resin including a step of preparing an aqueous monomer solution, a polymerization step, an optional step of crushing a hydrogel, a step of drying a hydrogel, an optional step of crushing after drying, a classification step, and a surface crosslinking step, and using a solubilized polymer obtained by a solubilization method as a part of the raw material.

[0061] Specific embodiments of the present production method will be described in detail below, taking as an example a method including a step of preparing an aqueous monomer solution, a polymerization step, an optional step of crushing a hydrogel, a step of drying the hydrogel, an optional step of crushing after drying, a classification step, and a surface crosslinking step.

[0062] (2-1) Preparation of monomer aqueous solution The present production method preferably includes a monomer aqueous solution preparation step of preparing an aqueous solution containing acrylic acid (salt) as a main component (hereinafter referred to as "monomer aqueous solution"). In the present production method, a monomer slurry liquid can be used in addition to the monomer aqueous solution within a range in which the water absorption performance of the obtained water absorbent resin is not deteriorated, but for the sake of convenience, the monomer aqueous solution will be described in this section.

[0063] The above-mentioned "main component" means that the amount (content) of acrylic acid (salt) used is 50 mol% or more in the total amount (100 mol%) of monomers (in other words, monomers contained in the aqueous monomer solution, excluding the internal crosslinking agent) to be subjected to the polymerization reaction of the water absorbent resin. The content of acrylic acid (salt) in the total amount (100 mol%) of monomers is preferably 70 mol% or more, and more preferably 90 mol% or more (upper limit: 100 mol%).

[0064] (acrylic acid) In the present production method, from the viewpoint of the physical properties and productivity of the resulting water absorbent resin, acrylic acid and / or its salt (hereinafter referred to as "acrylic acid (salt)") is used as a monomer serving as a raw material for the water absorbent resin. As such "acrylic acid", any known acrylic acid can be used.

[0065] The term "acrylate" refers to acrylic acid neutralized with a basic composition. The acrylate may be a commercially available acrylate (e.g., sodium acrylate) or may be one obtained by neutralization in a water absorbent resin manufacturing plant.

[0066] (Basic Composition) In the present specification, the term "basic composition" refers to a composition containing a basic compound. More specifically, the basic compound may be an alkali metal carbonate and / or hydrogen carbonate, an alkali metal hydroxide, ammonia, an organic amine, or the like. Among these, from the viewpoint of the physical properties of the obtained water absorbent resin, a strongly basic basic compound, for example, an alkali metal hydroxide such as sodium hydroxide, potassium hydroxide, or lithium hydroxide, is preferred, and sodium hydroxide is more preferred.

[0067] (neutralization) In the present production method, it is preferable to neutralize at least a part of the acrylic acid. As the neutralization in the present production method, either neutralization of the acrylic acid (before polymerization) or neutralization of the hydrogel crosslinked polymer obtained by crosslinking and polymerizing the acrylic acid (after polymerization) (hereinafter referred to as "post-neutralization") can be selected or used in combination. In addition, the mode of these neutralizations is not particularly limited, and may be continuous or batchwise, but continuous is preferable from the viewpoint of production efficiency, etc.

[0068] Regarding the conditions such as the neutralization apparatus, neutralization temperature, and residence time, the conditions described in International Publication No. 2009 / 123197 and US Patent Application Publication No. 2008 / 0194863 are also applied to the present invention.

[0069] The neutralization rate of the monomer (monomer having an acid group including acrylic acid) in the present production method is preferably 10 to 90 mol%, more preferably 40 to 85 mol%, further preferably 50 to 80 mol%, and particularly preferably 60 to 75 mol% in the total amount of the acid groups of the monomer (100 mol%). By setting the neutralization rate to 10 mol% or more, a water absorbent resin having a sufficient water absorption capacity can be provided, and by setting the neutralization rate to 90 mol% or less, a water absorbent resin having a higher water absorption capacity under pressure can be provided. The neutralization rate of the aqueous monomer solution will be further explained by taking as an example a case where the aqueous monomer solution contains only acrylic acid as a monomer component. In this case, the neutralization rate of the monomer is 75 mol% means that the monomer component contained in the aqueous monomer solution is a mixture of 25 mol% acrylic acid and 75 mol% acrylic acid salt. Such a mixture may be called a partially neutralized product of acrylic acid.

[0070] The above neutralization rate is the same in the case of post-neutralization. The above neutralization rate is also applied to the neutralization rate of the water-absorbent resin as a final product. In the present manufacturing method, the solubilized polymer derived from the recovered water-absorbent resin is used as a part of the raw material in the manufacture of the water-absorbent resin. When the solubilized polymer derived from such a recovered water-absorbent resin is used as a part of the raw material in the manufacture of the water-absorbent resin, the solubilized polymer may contain a basic compound derived from the recovered water-absorbent resin. Then, this basic compound may neutralize the acrylic acid before polymerization or the hydrogel-like crosslinked polymer after polymerization. Therefore, it is preferable to adjust the neutralization (post-neutralization) rate of the monomer in the aqueous monomer solution, the hydrogel-like polymer, and the water-absorbent resin as a final product to a predetermined range, taking into account the neutralization by the basic compound derived from the recovered water-absorbent resin.

[0071] (Other monomers) The aqueous monomer solution may contain a monomer (other monomer) other than the acrylic acid (salt). In the present production method, such other monomer can be used in combination with the acrylic acid (salt) to produce a water-absorbing resin.

[0072] The other monomer may be a water-soluble or hydrophobic unsaturated monomer. Specifically, an anionic unsaturated monomer such as (anhydrous) maleic acid, fumaric acid, crotonic acid, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, 2-(meth)acryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, or 2-hydroxyethyl (meth)acryloyl phosphate and / or a salt thereof may be suitably used as the other monomer. Moreover, one type of these other monomers may be used alone, or two or more types may be used in combination.

[0073] (Internal crosslinking agent) The aqueous monomer solution preferably contains an internal crosslinking agent. As the internal crosslinking agent that can be contained in the aqueous monomer solution, for example, the compounds described in U.S. Patent No. 6,241,928 can be mentioned. Among these, one or more compounds can be used as the internal crosslinking agent in consideration of reactivity.

[0074] In addition, from the viewpoint of the water absorption performance of the obtained water absorbent resin, the internal crosslinking agent is preferably a compound having two or more polymerizable unsaturated groups, more preferably a compound having thermal decomposition properties at the drying temperature described below, and further preferably a compound having two or more polymerizable unsaturated groups having a (poly)alkylene glycol structural unit.

[0075] The polymerizable unsaturated group is preferably, for example, an allyl group or a (meth)acrylate group, more preferably a (meth)acrylate group. The (poly)alkylene glycol structural unit is preferably polyethylene glycol, and the number n is preferably 1 to 100, more preferably 6 to 50.

[0076] The amount of the internal crosslinking agent used (content in the aqueous monomer solution) is preferably 0.0001 to 10 mol %, more preferably 0.001 to 1 mol %, based on the total amount of monomers. By setting the amount of the internal crosslinking agent used within the above range, a water-absorbing resin having a desired water-absorbing performance can be obtained. If the amount of the internal crosslinking agent used is less than 0.0001 mol %, the gel strength of the resulting water-absorbing resin tends to decrease and the water-soluble content tends to increase excessively, and if the amount of the internal crosslinking agent used is more than 10 mol %, the water-absorbing capacity of the resulting water-absorbing resin tends to decrease, which is not preferable. The mol % based on the total amount of monomers refers to the percentage of the number of moles of the internal crosslinking agent based on the total number of moles of monomers contained in the aqueous monomer solution.

[0077] In the present production method, a method is preferably applied in which a predetermined amount (within the above range) of an internal crosslinking agent is added in advance to the aqueous monomer solution, and the crosslinking reaction is started simultaneously with the polymerization. On the other hand, in addition to the above method, a method of post-crosslinking by adding an internal crosslinking agent during and / or after polymerization; a method of radical crosslinking using a radical polymerization initiator; a method of radiation crosslinking using active energy rays such as electron beams and ultraviolet rays, etc. can also be adopted. These methods can also be used in combination.

[0078] (Polymerization inhibitor) From the viewpoint of the polymerizability of acrylic acid and the color tone of the water absorbent resin, the aqueous monomer solution preferably contains a polymerization inhibitor in an amount of 200 ppm or less, more preferably 10 to 160 ppm, and even more preferably 20 to 100 ppm. The polymerization inhibitor is not particularly limited, but is preferably a methoxyphenol, more preferably p-methoxyphenol.

[0079] The aqueous monomer solution according to the present invention may contain impurities derived from each component in the aqueous monomer solution. For example, the description of the compounds described in U.S. Patent Application Publication No. 2008 / 0161512 regarding impurities derived from acrylic acid may also be applied to the present invention.

[0080] (Other substances) The aqueous monomer solution may contain substances (other substances) other than the above-mentioned components from the viewpoint of improving the physical properties of the resulting water-absorbing resin.

[0081] Examples of other substances include hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol, polyacrylic acid (salts), and crosslinked polyacrylic acid (salts); and other additives such as foaming agents such as carbonates and azo compounds, surfactants, chelating agents, and chain transfer agents.

[0082] When the aqueous monomer solution contains a hydrophilic polymer as an additional substance, the content of the hydrophilic polymer is preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less (the lower limit is 0% by mass) relative to the total amount (100% by mass) of the aqueous monomer solution. When the aqueous monomer solution contains other additives as additional substances, the content of the other additives is preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less (the lower limit is 0% by mass) relative to the total amount (100% by mass) of the aqueous monomer solution.

[0083] The above-mentioned other substances may be added to the reaction system in the polymerization step described below. In this case, it is preferable that the total amount of the other substances contained in the aqueous monomer solution and the other substances added to the reaction system in the polymerization step is within the above-mentioned range.

[0084] When a water-soluble resin or a water-absorbent resin is used as the hydrophilic polymer, a graft polymer or a water-absorbent resin composition (e.g., a starch-acrylic acid polymer, a PVA-acrylic acid polymer, etc.) is obtained. These polymers and water-absorbent resin compositions also fall within the scope of one embodiment of the present invention.

[0085] (2-2) Polymerization process The present production method preferably includes a polymerization step of polymerizing the monomers (particularly, acrylic acid (salt)-based monomers) in the aqueous monomer solution obtained in the aqueous monomer solution preparation step to obtain a hydrous gel-like crosslinked polymer (hereinafter referred to as "hydrous gel").

[0086] (Polymerization initiator) In the polymerization step, it is preferable to carry out a polymerization reaction of the monomer using a polymerization initiator. The polymerization initiator used in the polymerization step is appropriately selected depending on the polymerization form and the like, and is not particularly limited. For example, a thermal decomposition type polymerization initiator, a photodecomposition type polymerization initiator, or a redox type polymerization initiator used in combination with a reducing agent that promotes the decomposition of these polymerization initiators can be mentioned. Specifically, one or more of the polymerization initiators disclosed in U.S. Pat. No. 7,265,190 can be suitably used. In addition, from the viewpoint of handling and the physical properties of the obtained water-absorbing resin, the polymerization initiator is preferably a peroxide or an azo compound, more preferably a peroxide, and even more preferably a persulfate.

[0087] The amount of the polymerization initiator used in the polymerization step is preferably 0.001 to 1 mol %, more preferably 0.001 to 0.5 mol %, based on the total amount of monomers to be polymerized (monomers contained in the aqueous monomer solution). When a reducing agent is used in combination (i.e., when a redox polymerization initiator is used), the amount of the reducing agent used is preferably 0.0001 to 0.02 mol % based on the total amount of monomers. The mol % based on the monomer refers to the percentage of the number of moles of the polymerization initiator or reducing agent based on the total number of moles of monomers contained in the aqueous monomer solution.

[0088] In addition, instead of the above polymerization initiator, the polymerization reaction may be carried out by irradiation with active energy rays such as radiation, electron beams, and ultraviolet rays, or the polymerization reaction may be carried out by using these active energy rays in combination with the polymerization initiator.

[0089] (polymerization form) The polymerization form in the polymerization step is not particularly limited, but from the viewpoint of the water absorption properties of the obtained water absorbent resin and the ease of polymerization control, etc., preferably, spray droplet polymerization, aqueous solution polymerization, reversed phase suspension polymerization, more preferably aqueous solution polymerization, reversed phase suspension polymerization, and even more preferably aqueous solution polymerization are mentioned. Among them, continuous aqueous solution polymerization is particularly preferable. Forms such as continuous belt polymerization and continuous kneader polymerization can also be applied. In addition, a foaming polymerization form in which bubbles (particularly inert gas, etc.) are dispersed in a monomer aqueous solution to carry out polymerization can also be applied.

[0090] As specific polymerization forms, continuous belt polymerization is disclosed in U.S. Patent Nos. 4,893,999, 6,241,928, U.S. Patent Application Publication No. 2005 / 215734, etc., and continuous kneader polymerization is disclosed in U.S. Patent Nos. 6,987,151, 6,710,141, etc. By adopting these continuous aqueous solution polymerizations, the production efficiency of the water absorbent resin can be improved.

[0091] In addition, preferred forms of the continuous aqueous solution polymerization include "high-temperature initiated polymerization" and "high-concentration polymerization." "High-temperature initiated polymerization" refers to a form in which polymerization is initiated at a temperature of preferably 30°C or higher, more preferably 35°C or higher, even more preferably 40°C or higher, and particularly preferably 50°C or higher (upper limit is the boiling point). "High-concentration polymerization" refers to a form in which polymerization is performed at a monomer concentration of preferably 30% by mass or higher, more preferably 35% by mass or higher, even more preferably 40% by mass or higher, and particularly preferably 45% by mass or higher (upper limit is the saturated concentration). These polymerization forms can also be used in combination.

[0092] In the polymerization step, the polymerization can be carried out under a desired atmosphere, for example, under an air atmosphere, but from the viewpoint of the color tone of the obtained water absorbent resin, it is preferable to carry out the polymerization under an inert gas atmosphere such as nitrogen or argon. In this case, it is preferable to control the oxygen concentration to 1 volume % or less. It is also preferable to replace the dissolved oxygen in the aqueous monomer solution with an inert gas (for example, to make the dissolved oxygen less than 1 mg / l).

[0093] In one embodiment of the present invention, the polymerization may be carried out as foaming polymerization in which bubbles (particularly the above-mentioned inert gases or the like) are dispersed in an aqueous monomer solution.

[0094] (2-3) Hydrogel crushing process The present production method preferably optionally includes a hydrous gel crushing step in which the hydrous gel obtained in the polymerization step is crushed by a screw extruder such as a kneader or a meat chopper, or a gel crusher such as a cutter mill, to obtain a particulate hydrous gel (hereinafter referred to as a "particulate hydrous gel"). When kneader polymerization is used as the polymerization form in the polymerization step, the polymerization step and the gel crushing step are carried out simultaneously. In addition, when a particulate hydrous gel is obtained directly in the polymerization process, such as in gas phase polymerization or reverse phase suspension polymerization, the hydrous gel crushing step may not be carried out.

[0095] Regarding gel crushing conditions and forms other than those described above, the contents disclosed in WO 2011 / 126079 are preferably applied to the present invention.

[0096] (2-4) Hydrogel drying process The present production method preferably includes a hydrous gel drying step in which the particulate hydrous gel obtained in the polymerization step and / or hydrous gel crushing step is dried to a desired resin solid content to obtain a dried polymer. The resin solid content of the dried polymer is determined from the loss on drying (the change in mass when 1 g of the dried polymer is heated at 180°C for 3 hours), and is preferably 80 mass% or more, more preferably 85 to 99 mass%, even more preferably 90 to 98 mass%, and particularly preferably 92 to 97 mass%.

[0097] The method for drying the particulate hydrogel is not particularly limited, and examples thereof include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, high humidity drying using high temperature water vapor, etc. Among these, from the viewpoint of drying efficiency, hot air drying is preferred, and band drying in which hot air drying is performed on a ventilation belt is more preferred.

[0098] The drying temperature (hot air temperature) in the hot air drying is preferably 120 to 250°C, more preferably 150 to 200°C, from the viewpoint of the color tone and drying efficiency of the obtained water-absorbent resin. The drying conditions other than the drying temperature, such as the hot air speed and drying time, can be appropriately set according to the water content and total mass of the particulate hydrogel to be dried and the intended resin solid content. When band drying is performed, the conditions described in International Publication Nos. 2006 / 100300, 2011 / 025012, 2011 / 025013, and 2011 / 111657 are appropriately applied as drying conditions.

[0099] (2-5) Grinding process after drying The present production method preferably includes a post-drying pulverization step of appropriately pulverizing the dried polymer in order to adjust the particle size of the dried polymer. In the post-drying pulverization step, the method of pulverizing the dried polymer is not particularly limited, and the pulverization step can be carried out using a high-speed rotary pulverizer such as a roll mill, a hammer mill, a screw mill, or a pin mill, a vibration mill, a knuckle type pulverizer, a cylindrical mixer, or the like.

[0100] (2-6) Classification process The present production method preferably includes a classification step of classifying the dried polymer obtained in the drying step or the pulverized product of the dried polymer obtained in the pulverization step after drying to obtain a particulate dried polymer of a desired particle size.

[0101] In the classification step, the method for classifying the dried polymer or its pulverized product includes sieve classification using a JIS standard sieve (JIS Z8801-1 (2000)), air flow classification, etc. Among them, from the viewpoint of classification efficiency, sieve classification is preferably selected.

[0102] The particle size of the particulate dried polymer obtained in the classification step is not particularly limited, but for example, the mass average particle size (D50) is preferably 200 to 500 μm, more preferably 2500 to 450 μm, and even more preferably 300 to 400 μm. Also, the proportion of particles smaller than 150 μm is preferably less than 5 mass%, more preferably 4 mass% or less, and even more preferably 3 mass% or less.

[0103] (2-7) Surface crosslinking process The present production method preferably includes a surface cross-linking step, which is a step of providing a portion with a higher cross-linking density on the surface layer (a portion several tens of μm from the surface of the particulate dry polymer) of the particulate dry polymer obtained through the above-mentioned classification step. The surface cross-linking step is composed of a mixing step, a heat treatment step, and a cooling step (optional).

[0104] In the surface cross-linking step, a surface-cross-linked water-absorbent resin (water-absorbent resin particles) is obtained by radical cross-linking, surface polymerization, cross-linking reaction with a surface cross-linking agent, or the like on the surface of the particulate dried polymer.

[0105] (Surface cross-linking agent) In the surface crosslinking step, it is preferable to crosslink the surface of the particulate dried polymer using a surface crosslinking agent. The surface crosslinking agent is not particularly limited, but may be an organic or inorganic surface crosslinking agent. Among them, from the viewpoint of the physical properties of the water-absorbent resin, the handling property of the surface crosslinking agent, etc., an organic surface crosslinking agent that reacts with a carboxyl group is preferable. Specifically, as the surface crosslinking agent, one or more compounds disclosed in U.S. Patent No. 7,183,456 can be used. More specifically, as the surface crosslinking agent, polyhydric alcohol compounds, epoxy compounds, haloepoxy compounds, polyvalent amine compounds or condensates thereof with haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, polyvalent metal salts, alkylene carbonate compounds, cyclic urea compounds, etc. may be used. One of these surface crosslinking agents may be used alone, or two or more may be used in combination. In addition, it is preferable to use these surface crosslinking agents in the state of an aqueous solution (i.e., in the state of a surface crosslinking liquid).

[0106] The amount of the surface crosslinking agent used in the surface crosslinking step (the total amount used when a plurality of agents are used) is preferably 0.01 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, based on 100 parts by mass of the particulate dry polymer. The surface crosslinking agent is preferably added in the form of an aqueous solution, and in this case, the amount of water used is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, based on 100 parts by mass of the particulate dry polymer. Furthermore, a hydrophilic organic solvent may be used in combination as necessary, and in that case, the amount of the hydrophilic organic solvent used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the particulate dry polymer. Each additive added in the "remoistening step" described later can also be mixed into the aqueous solution of the surface crosslinking agent within the range of 5 parts by mass or less.

[0107] (Mixing process) The surface crosslinking step includes a mixing step of mixing the particulate dry polymer with the above-mentioned surface crosslinking agent. The method of mixing the surface crosslinking agent in the mixing step is not particularly limited, but for example, a method of preparing a surface crosslinking agent solution in advance and mixing the solution with the particulate dry polymer by preferably spraying or dropping, more preferably spraying, can be mentioned.

[0108] The device for mixing the particulate dry polymer with the surface crosslinking agent is not particularly limited, but is preferably a high-speed stirring type mixer, more preferably a high-speed stirring type continuous mixer.

[0109] (Heat treatment process) The surface cross-linking step includes a heat treatment step in which the mixture discharged from the mixing step is heated to cause a cross-linking reaction on the surface of the particulate dry polymer. The heat treatment step can also be called a cross-linking reaction step.

[0110] The apparatus for carrying out the heat treatment is not particularly limited, but a paddle dryer is preferable. The heating temperature in the heat treatment, in other words, the reaction temperature in the crosslinking reaction, is appropriately set depending on the type of the surface crosslinking agent used, but is preferably 50 to 300°C, more preferably 100 to 200°C.

[0111] (cooling process) The surface cross-linking step preferably includes a cooling step of cooling the surface-cross-linked particulate dry polymer (that is, water-absorbent resin particles) after the heat treatment.

[0112] In the cooling step, the cooling device is not particularly limited, but is preferably a device having the same specifications as the device used in the heat treatment step, and more preferably a paddle dryer. This is because it can be used as a cooling device by changing the heat medium to a refrigerant. The water-absorbent resin particles obtained in the heat treatment step are forcibly cooled, if necessary, to preferably 40 to 80°C, more preferably 50 to 70°C in the cooling step.

[0113] (2-8) Use of solubilizing polymers In this manufacturing method, the solubilized polymer obtained by this solubilization method is used as a part of the raw material of the obtained water-absorbent resin. In this manufacturing method, "using the solubilized polymer as a part of the raw material of the obtained water-absorbent resin" means that the water-soluble polymer obtained by this solubilization method is added to the water-absorbent resin raw material (e.g., monomer aqueous solution, water-containing gel, dried polymer, and / or particulate dried polymer) in any of the manufacturing steps of the water-absorbent resin that the above-mentioned manufacturing method may include, specifically, in any of the steps of preparing the monomer aqueous solution, the polymerization step, the hydrogel crushing step, the hydrogel drying step, the crushing step after drying, the classification step, and the surface crosslinking step.

[0114] Methods for adding the solubilized polymer obtained by the present solubilization method in the above-mentioned process include, but are not limited to, adding it as an aqueous solution, adding it as a powder after drying once, or adding it in the form of a slurry with some undissolved material remaining.

[0115] More specifically, when the solubilized polymer obtained by the present solubilization method is added in the "process for preparing an aqueous monomer solution", the solubilized polymer obtained by the present solubilization method may be mixed into the aqueous monomer solution, or the solubilized polymer obtained by the present solubilization method may be mixed in advance with water and then mixed with other raw materials. From the viewpoint of uniform mixing of the raw materials, it is preferable to mix the solubilized polymer obtained by the present solubilization method into the aqueous monomer solution. The solubilized polymer may also be added in the form of an aqueous solution or dispersion of the solubilized polymer. The solubilized polymer (and its aqueous solution) may also be added in a state in which it has been heated to 50°C or higher in advance.

[0116] When the solubilized polymer obtained by the present solubilization method is added in the "polymerization step", the solubilized polymer obtained by the present solubilization method may be added before or after the start of polymerization. From the viewpoint of uniformity of the polymer component, it is preferable to add the solubilized polymer obtained by the present solubilization method before the start of polymerization. In this case, the solubilized polymer may also be added in the form of an aqueous solution or dispersion of the solubilized polymer.

[0117] When the solubilized polymer obtained by the present solubilization method is added in the "hydrogel crushing step", the solubilized polymer obtained by the present solubilization method may be added before crushing or during crushing. It may also be added in portions. From the viewpoint of uniformity of the gel component, it is preferable to add the solubilized polymer obtained by the present solubilization method before gel crushing.

[0118] When the solubilized polymer obtained by the present solubilization method is added in the "water-containing gel drying step", the water-containing gel and the solubilized polymer obtained by the present solubilization method may be mixed either before or after drying.

[0119] When the solubilized polymer obtained by the present solubilization method is added in the "classification step", the dried polymer and the solubilized polymer obtained by the present solubilization method may be mixed before classification, or may be mixed after classification. From the viewpoint of uniformity of particle size, it is preferable to add the solubilized polymer obtained by the present solubilization method before classification.

[0120] When the solubilized polymer obtained by the present solubilization method is added in the "surface cross-linking step", the water-absorbent resin dried in advance may be mixed with the solubilized polymer obtained by the present solubilization method, or they may be mixed after surface cross-linking. From the viewpoint of uniform mixing of the surface cross-linking liquid and the water-absorbent resin, it is preferable to use the powdered solubilized polymer obtained by the present solubilization method and subject all the surface-cross-linked materials (i.e., the particulate dried polymer and the powdered solubilized polymer obtained by the present solubilization method) to surface cross-linking in the form of powder. In addition, when the solubilized polymer obtained by the present solubilization method is mixed after surface cross-linking, it is preferable to use the solubilized polymer obtained by the present solubilization method, which is at least partially surface-cross-linked.

[0121] In the present production method, the solubilized polymer obtained by the present solubilization method may be added at any of the above timings, but is preferably added before the drying step, since this allows for high complexation of the solubilized polymer with the water absorbent resin (in other words, a small amount of elution as water-soluble matter). In addition, the entire amount of the solubilized polymer obtained by the present solubilization method to be added may be added at once at any timing, or may be added in portions at multiple timings. In addition, the solubilized polymer obtained by the present solubilization method may be added in different forms depending on the timing of addition.

[0122] In the present production method, the ratio of the solubilized polymer obtained by the present solubilization method to all the water-absorbent resin raw materials is not particularly limited, but is preferably 1 to 60 mass%, more preferably 1 to 50 mass%, even more preferably 1 to 40 mass%, and even more preferably 1 to 30 mass%. In other words, in the present production method, it is preferable to add the solubilized polymer obtained by the present solubilization method so that the ratio of the solubilized polymer obtained by the present solubilization method to all the water-absorbent resin raw materials is within the above range. In addition, in this specification, "all the water-absorbent resin raw materials" refers to all the raw materials used in the production process of the water-absorbent resin (i.e., the total amount of the solubilized polymer obtained by the present solubilization method to be added and the water-absorbent resin prepared from the aqueous monomer solution). More specifically, the raw materials include the solubilized polymer, and the non-recycled water-absorbent resin and its raw materials (e.g., acrylic acid (salt); basic composition; other monomers; internal crosslinking agents; other substances (starch, etc.); polymerization initiators; and surface crosslinking agents, etc.). The above ratio is the ratio of the solid content of the solubilized polymer obtained by the present solubilization method to the solid content of all the raw materials for the water-absorbent resin.

[0123] (2-9) Colorability (yellowness index / YI value) of water absorbent resin obtained by this production method The YI value of the water-absorbent resin obtained by the present production method is preferably 20.0 or less, more preferably 18.0 or less, and even more preferably 16.0 or less. The lower limit of the YI value is not particularly limited and may be 0. The YI value of the water-absorbent resin is an index showing the colorability of the water-absorbent resin, and the YI value of the water-absorbent resin within the above range means that the coloring of the water-absorbent resin is more suppressed. The YI value of the water-absorbent resin can be measured by the method described in the Examples.

[0124] (2-10) Water absorption properties of the water absorbent resin obtained by this production method The water absorption properties of the water absorbent resin obtained by this manufacturing method are preferably CRC of 25 g / g or more, more preferably 30 g / g or more, even more preferably 35 g / g or more, and even more preferably 40 g / g or more. Also, AAP (0.3 psi) is preferably 10 g / g or more, more preferably 15 g / g or more, more preferably 20 g / g or more, more preferably 22 g / g or more, even more preferably 24 g / g or more, and even more preferably 26 g / g or more. The CRC and AAP (0.3 psi) of the water absorbent resin can be measured by the method described in the Examples.

[0125] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. EXAMPLES

[0126] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the present invention is not limited to these examples. Examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention.

[0127] (a) Solids concentration of solubilized polymer The solids concentration of the solubilized polymer (aqueous solution) obtained in the Examples and Comparative Examples was measured by the following method.

[0128] Specifically, first, a solubilized polymer aqueous solution with a mass Wa (g) was placed on an aluminum dish with a mass Wb (g) and dried for 3 hours in a hot air circulating oven at 180°C. The total mass Wc (g) of the solubilized polymer and the aluminum dish after drying was measured. The solids concentration of the solubilized polymer aqueous solution was calculated according to the following formula (1).

[0129] Solids concentration (mass%) of solubilized polymer aqueous solution = {(mass Wc - mass Wb) / mass Wa} × 100 Equation (1).

[0130] (b) Mass average molecular weight (Mw) of the solubilizing polymer The weight average molecular weight (Mw) of the solubilized polymers obtained in the examples and comparative examples was measured according to the following procedure.

[0131] (Preparation of measurement samples) First, the solubilized polymer was dissolved in the following solvent to prepare a solution with a concentration of 0.1% by mass. The obtained solubilized polymer solution was then passed through a filter (GL Sciences: GL Chromatodisk, aqueous 25A, pore size 0.2 μm) to prepare a measurement sample.

[0132] Solvent: Aqueous solution containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM sodium dihydrogen phosphate dodecahydrate, and 400 ppm sodium azide (pH 6.35-6.38). Using the measurement sample, GPC measurement was carried out under the following measurement conditions.

[0133] (GPC measurement) The above-mentioned measurement sample was subjected to GPC measurement using a Viscotec TDAmax manufactured by Malvern Instruments. The measurement device was equipped with a size exclusion chromatograph, a refractive index detector, a light scattering detector and a capillary viscometer. The measurement device and measurement conditions were as follows.

[0134] Pump, autosampler: Viscotec GPCmax (Malvern) Guard column: OHpak SB-G (Showa Denko Co., Ltd.) Column: OHpak SB-806MHQ (Showa Denko K.K.), two columns connected in series Detector: Viscotec TDAmax (Malvern) Solvent: Aqueous solution containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM sodium dihydrogen phosphate dodecahydrate, and 400 ppm sodium azide (pH 6.35-6.38). Flow rate: 0.5ml / min Injection volume: 100μl.

[0135] The water used in the GPC measurements was pure water from which impurities had been thoroughly removed. The GPC measurements were performed under conditions where the detector baseline was stable, particularly when there were no noise peaks in the light scattering detector.

[0136] The measuring device was calibrated using polyoxyethylene glycol (mass average molecular weight (Mw): 21966, molecular weight distribution (Mw / Mn): 1.0, differential refractive index (dn / dc): 0.132, solvent refractive index: 1.33) as a standard sample.

[0137] The differential refractive index (dn / dc) of the solubilized polymer to be measured was set to 0.12, and the solvent refractive index was set to 1.33. Data collection and analysis of the refractive index, light scattering intensity, and viscosity were performed using software (Viscotek OmniSEC4.7.0 (registered trademark)).

[0138] Based on the data obtained from the refractive index (RI), light scattering intensity (angle: 7°) (LALS), and viscometer (DP) measurements, the mass average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (Mw / Mn) of the solubilized polymer were calculated.

[0139] (c) Color evaluation of solubilized polymer aqueous solution (YI value / yellowness index) The coloring of the solubilized polymer aqueous solutions obtained in the Examples and Comparative Examples was evaluated using a spectrophotometer (Spectrophotometer SE7700) manufactured by Nippon Denshoku Industries Co., Ltd.

[0140] Specifically, first, about 16 g of the solubilized polymer aqueous solution was filled into the square cell and placed in the holder in the transmission sample chamber. The YI value (Yellow Index) of the solubilized polymer aqueous solution was measured using the spectrophotometer under conditions of room temperature (20-25°C) and humidity of 50 RH%. Transmission measurement was selected as the measurement setting condition. In addition, an accessory square cell (light path 10 mm) was used, and industrial pure water was used for standard calibration.

[0141] (d) Coloring evaluation of water absorbent resin (YI value / yellowness index) The coloring of the water-absorbing resins produced using the solubilized polymers obtained in the Examples and Comparative Examples as part of the raw materials was evaluated using a spectrophotometer (Spectrophotometer SE7700) manufactured by Nippon Denshoku Industries Co., Ltd.

[0142] Specifically, the YI value (Yellow Index) of the water-absorbent resin was measured by the spectrophotometer under the conditions of room temperature (20 to 25°C) and humidity of 50 RH%. Reflection measurement was selected as the measurement setting condition, and the measurement diameter was LAV (28 mm). In addition, the attached 35Φ×15H round cell, 35Φ×15H cell case, and standard white board for powder were used.

[0143] (e) Amount of remaining decomposition agent (amount of remaining hydrogen peroxide) The amount of hydrogen peroxide remaining in the aqueous solubilized polymer solutions obtained in the Examples and Comparative Examples was calculated by coloring hydrogen peroxide with titanium(IV) sulfate, a color reagent, and measuring the absorbance according to the following procedure.

[0144] Specifically, 0.50 g of the solubilized polymer aqueous solution, 8.5 g of industrially pure water, and 1.0 g of a 10% by mass calcium chloride aqueous solution were mixed and the solubilized polymer was precipitated, and then filtered through a 0.2 μm chromatodisc. 0.30 g of 1 mol / L sulfuric acid (2N) was added to the filtrate and mixed, after which the color was developed with 0.10 g of 30% by mass titanium sulfate (IV).

[0145] The absorbance was measured at a wavelength of 410 nm using a ratio beam spectrophotometer U-5100 (manufactured by Hitachi High-Technologies Corporation) (using the attached 10 mm square cell) with industrial pure water as the standard.

[0146] On the other hand, a calibration curve was prepared with a known concentration and reacted with titanium(IV) sulfate in the same manner as above to prepare a calibration curve of hydrogen peroxide amount vs. absorbance. Using the prepared calibration curve, the "amount of hydrogen peroxide remaining in the solubilized polymer aqueous solution" was calculated from the absorbance.

[0147] (f) CRC The "CRC" of a water-absorbent resin is an abbreviation for "Centrifuge Retention Capacity" and indicates the absorption capacity (unit: g / g) of a water-absorbent resin for 30 minutes under no pressure with respect to a 0.90% by mass aqueous solution of sodium chloride. The method for measuring the CRC of a specific water-absorbent resin (a water-absorbent resin manufactured using a solubilized polymer as part of the raw material) was as follows.

[0148] 0.200 g of the water-absorbent resin was uniformly placed in a bag (85 mm x 60 mm) made of nonwoven fabric (manufactured by Nangoku Pulp Kogyo Co., Ltd., product name: Heatlon Paper, model: GSP-22) and heat-sealed. The bag (containing the water-absorbent resin) was immersed in a large excess (usually about 500 ml) of 0.90% by mass sodium chloride aqueous solution at room temperature. After 30 minutes, the bag was pulled out and drained for 3 minutes using a centrifuge (manufactured by Kokusan Co., Ltd., centrifuge: model H-122) at a centrifugal force (250 G) described in Edana ABSORBENCY II 441.1-99, and the mass W1 (g) of the bag was measured. In addition, the same operation was performed without using the water-absorbent resin, and the mass W0 (g) at that time was measured. From the measured values ​​of W1 and W0, the CRC of the control water-absorbent resin was calculated according to the following formula (2): CRC of absorbent resin (g / g) = (W1-W0) / (mass of absorbent resin (g)-1) Equation (2).

[0149] (g) AAP0.3 The "AAP" of a water-absorbent resin is an abbreviation for "Absorption Against Pressure" and indicates the absorbency (unit: g / g) against a 0.90% by mass aqueous sodium chloride solution. Also, "AAP0.3" means the AAP under a pressure of 0.3 psi.

[0150] The AAP0.3 of a specific water-absorbent resin (a water-absorbent resin produced using a solubilized polymer as part of the raw material) was measured in accordance with NWSP 242.0.R2(15) except that the pressure condition was changed from 0.7 psi to 0.3 psi. More specifically, a large excess of 0.9% by mass sodium chloride aqueous solution was used, and 0.9 g of the water-absorbent resin was subjected to pressure of 2.07 kPa (21 g / cm) for 1 hour. 2 After swelling under a pressure of 0.2 psi (0.3 psi), the AAP (absorbency against pressure) was measured.

[0151] (h) Mass average particle size of hydrous gel and mass average particle size when converted into dry matter h-1) Mass average particle size of hydrogel The mass average particle size of the hydrogel in the examples and comparative examples was measured by the following method.

[0152] 1.0 g of hydrogel particles (solid content α% by mass) at a temperature of 20 to 25°C was added to 1000 g of deionized water (hereinafter referred to as "EMAL aqueous solution") containing 0.08% by mass of EMAL 20C (surfactant, manufactured by Kao Corporation) to prepare a dispersion. A stirrer tip of 50 mm in length and 7 mm in diameter was placed in the dispersion, and the mixture was stirred at 300 rpm for 60 minutes (a cylindrical polypropylene container of about 1.14 L, 21 cm in height and 8 cm in diameter was used).

[0153] After stirring, the above dispersion was poured into the center of a JIS standard sieve (diameter 21 cm, sieve openings: 8 mm / 4 mm / 2 mm / 1 mm / 0.60 mm / 0.30 mm / 0.15 mm / 0.075 mm) placed on a rotating plate. After washing out all the hydrous gel onto the sieve using 200 g of an aqueous solution of EMAL, 6,000 g of the aqueous solution of EMAL was poured from above using a shower (72 holes, liquid volume: 6.0 L / min) from a height of 30 cm to a water injection range (50 cm). 2 ) was poured evenly onto the sieve so that it was evenly distributed over the entire surface, and the hydrous gel was classified. The hydrous gel on the first sieve was drained for about 2 minutes and then weighed. The second and subsequent sieves were also classified in the same manner, and the hydrous gel remaining on each sieve after draining was weighed.

[0154] The mass% ratio was calculated from the mass of the hydrous gel remaining on each sieve using the following formula (3). In addition, the mesh size of the sieve after draining was plotted on a logarithmic probability paper according to the following formula (4). The particle size at which the cumulative sieve %R of the plot corresponds to 50 mass% was taken as the mass average particle size of the hydrous gel (Gel D50).

[0155] X(%)=(w / W)×100 ··· Formula (3) R(α)(mm)=(20 / w) 1 / 3 ×r...Equation (4) Here, X: Mass% (%) of the hydrous gel remaining on each sieve after classification and draining w: Mass (g) of the hydrogel remaining on each sieve after classification and draining W: Total mass (g) of the hydrogel remaining on each sieve after classification and draining R(α): Sieve opening (mm) when converted into a hydrous gel with a solid content of α% by mass r: The mesh size (mm) of the sieve through which the hydrogel swollen in the emal aqueous solution was classified It is.

[0156] h-2) Mass average particle size calculated as dry matter The mass average particle diameter (Solid D50) of the hydrogel calculated as a dry matter (solid content 100% by mass) was calculated from the mass average particle diameter (Gel D50) of the hydrogel and the solid content concentration (% by mass) of the hydrogel according to the following formula (5).

[0157] (Solid D50) = (Gel D50) × {(Solid concentration of hydrous gel particles) / 100} 1 / 3 ··· Equation (5) [Production Example 1] A reaction liquid was prepared by dissolving 0.44 parts by mass of polyethylene glycol diacrylate (molecular weight: 523) in 550 parts by mass of a 38% by mass aqueous solution of sodium acrylate (neutralization rate: 71 mol%), and the reaction liquid was degassed for 30 minutes under a nitrogen gas atmosphere.

[0158] The reaction liquid was then fed to a jacketed stainless steel twin-arm kneader having two sigma-type blades with an openable lid, and the system was replaced with nitrogen gas while maintaining the liquid temperature at 30°C. Next, 0.24 parts by mass of ammonium persulfate and 0.012 parts by mass of L-ascorbic acid were added while stirring the liquid in the kneader, and the polymerization reaction started about 1 minute later. This polymerization was carried out at 30 to 95°C, and a hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel") was taken out 60 minutes after the start of polymerization.

[0159] The obtained hydrogel was dried with hot air at 150° C. for 100 minutes, pulverized using a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm to obtain an irregularly pulverized water-absorbent resin precursor (1). The mass average particle diameter of the water-absorbent resin precursor (1) was 400 μm.

[0160] 1800 parts by mass of 0.9% by mass sodium chloride aqueous solution (physiological saline) was added to 200 parts by mass of the obtained water absorbent resin precursor (1), and the mixture was left at room temperature for 8 hours or more to prepare a simulated used water absorbent resin (1). The mass average particle diameter (Solid D50) of the simulated used water absorbent resin (1) calculated as a dry product was 397 μm.

[0161] [Comparative Example 1] Into a reaction vessel, 200.0 g of the simulated used water absorbent resin (1) obtained in Production Example 1 and 30.0 g of a 15% by mass aqueous solution of sodium carbonate as a pH adjuster were added, and thoroughly mixed with a spatula. Next, 1.33 g of a 30% by mass aqueous solution of hydrogen peroxide as a decomposition agent was added, and further thoroughly mixed with a spatula. Here, a part of the mixture in the reaction vessel was taken out, and a pH test paper was attached to it, and it was confirmed that the pH of the mixture was 8.0 to 8.5.

[0162] Next, the reaction vessel containing the mixture was immersed in a thermostatic bath at 80°C to initiate the decomposition reaction. After one hour had passed, the decomposition status of the mixture was checked using a spatula, and some of the mixture remained as a gel-like substance without being decomposed. After the decomposition reaction was continued for another hour (total time: 2 hours), the decomposition status of the mixture was checked using a spatula, and no gel-like substance was confirmed, and almost all of the simulated used water absorbent resin (1) was solubilized. This solubilized simulated used water absorbent resin (1) was designated as solubilized polymer (C1).

[0163] The pH of the solubilized polymer (C1) aqueous solution was measured with a pH meter (pH meter: LAQUA act D-71 manufactured by Horiba, Ltd.) and found to be 8.11. The solubilized polymer (C1) aqueous solution had a solid content of 8.14% by mass, a YI value of 3.41, and a mass average particle diameter Mw of 501,000.

[0164] Next, in order to remove the decomposing agent (hydrogen peroxide) remaining in the solubilized polymer (C1) aqueous solution, 16.2 g of a 15% by mass aqueous sodium carbonate solution was added and stirred for 3 hours while maintaining the temperature at 25° C. Thereafter, the amount of hydrogen peroxide remaining in the aqueous solution was measured and found to be 41 ppm, confirming that almost all of the hydrogen peroxide had been removed.

[0165] [Comparative Example 2] A solubilized polymer (C2) was obtained by carrying out the decomposition treatment in the same manner as in Comparative Example 1, except that the decomposition treatment temperature was changed from 80° C. to 100° C. In Comparative Example 2, almost all of the simulated used water absorbent resin (1) was solubilized when the decomposition treatment time reached 1 hour.

[0166] The pH of the solubilized polymer (C2) aqueous solution was measured with a pH meter and found to be 8.05. The solubilized polymer (C2) aqueous solution had a solids concentration of 9.03% by mass, a YI value of 3.82, and a mass average particle diameter Mw of 486,000.

[0167] Next, in the same manner as in Comparative Example 1, 16.2 g of a 15% by mass aqueous sodium carbonate solution was added, and the mixture was stirred for 3 hours while maintaining the temperature at 25° C., thereby removing the decomposing agent (hydrogen peroxide) remaining in the aqueous solution.

[0168] [Comparative Example 3] A decomposition treatment was carried out in the same manner as in Comparative Example 1, except that 30.0 g of a 15% by mass aqueous sodium carbonate solution was not used as a pH adjuster. However, when the reaction vessel was immersed in a thermostatic bath at 80°C for 2 hours, the simulated used water absorbent resin (1) was hardly solubilized, and a solubilized polymer could not be obtained under the conditions of Comparative Example 3. At this time, it was confirmed that the pH of the mixture in the vessel was 6.0 to 6.5.

[0169] [Comparative Example 4] A decomposition treatment was carried out in the same manner as in Comparative Example 1, except that the amount of the 15 mass% sodium carbonate aqueous solution, which was the pH adjuster, was changed from 30.0 g to 46.1 g. However, when the reaction vessel was immersed in a thermostatic bath at 80°C for 2 hours, the simulated used water absorbent resin (1) was hardly solubilized, and a solubilized polymer could not be obtained under the conditions of Comparative Example 4. At this time, it was confirmed that the pH of the mixture in the vessel was more than 8.5 and not more than 9.0.

[0170] [Comparative Example 5] A decomposition treatment was carried out in the same manner as in Comparative Example 1, except that 1.33 g of a 30 mass% aqueous hydrogen peroxide solution as a decomposition agent was replaced with 3.34 g of L-ascorbic acid and 0.46 g of iron sulfate heptahydrate, and 30.0 g of a 15 mass% aqueous sodium carbonate solution as a pH adjuster was not used, to obtain a solubilized polymer (C5). In Comparative Example 5, the simulated used water absorbent resin (1) was hardly solubilized at the time when the decomposition treatment time was 1 hour. On the other hand, at the time when the decomposition treatment time was 2 hours, most of the simulated used water absorbent resin (1) was solubilized, although some of it remained undissolved.

[0171] The pH of the solubilized polymer (C5) aqueous solution was measured with a pH meter and found to be 5.56. The solubilized polymer (C5) aqueous solution had a solid content of 9.45% by mass, a YI value of 89.7, and a mass average particle diameter Mw of 85,000.

[0172] [Example 1] (Small particle size process) 250.0 g of the simulated used water absorbent resin (1) obtained in Production Example 1 was placed in a mixer (Fann Constant Speed ​​Mixer Model 686CS) and subjected to shearing treatment at 6000 rpm for 30 seconds four times (particle size reduction step) to obtain a simulated used water absorbent resin (2). The gel particle size (Solid D50) of the simulated used water absorbent resin (1) was 397 μm, whereas the gel particle size (Solid D50) of the simulated used water absorbent resin (2) was 49 μm in terms of dry matter. That is, in the particle size reduction step, the gel particle size (Solid D50; 397 μm in terms of dry matter) of the simulated used water absorbent resin (1) was reduced to about 1 / 8 by the mixer treatment. Here, "the gel particle size of the water absorbent resin (simulated used water absorbent resin (2)) is 49 μm in terms of dry matter" means that, of all particles (100% by mass) of the water absorbent resin, the ratio of particles having a particle size of 49 μm or more and particles having a particle size of less than 49 μm is 50% by mass each. Therefore, for the simulated used water absorbent resin (2) obtained in Example 1, the ratio of particles having a particle size of 80 μm or less in terms of dry matter was more than 50% by mass, specifically, about 70% by mass.

[0173] (Solubilization process) The same decomposition treatment as in Comparative Example 1 was carried out (solubilization step), except that 200.0 g of the above-mentioned simulated used water absorbent resin (2) was used instead of 200.0 g of the simulated used water absorbent resin (1). It was confirmed that the pH of the mixture in Example 1 was 8.0 to 8.5. In Comparative Example 1, it took 2 hours to solubilize the entire amount of the simulated used water absorbent resin (1), but in Example 1, it took 1 hour to solubilize the entire amount (almost 100%) of the simulated used water absorbent resin (2). This solubilized simulated used water absorbent resin (2) was used as the solubilized polymer (1).

[0174] The pH of the solubilized polymer (1) aqueous solution was measured with a pH meter and found to be 8.09. The solubilized polymer (1) aqueous solution had a solids concentration of 9.05% by mass, a YI value of 3.83, and a mass average particle diameter Mw of 214,000.

[0175] Next, as in Comparative Example 1, 16.2 g of a 15% by mass aqueous solution of sodium carbonate was added, and the mixture was stirred for 3 hours while maintaining the temperature at 25° C., thereby removing the decomposing agent (hydrogen peroxide) remaining in the aqueous solution. In addition, in the production process of the solubilized polymer (1), no transition metal (such as Fe) or L-ascorbic acid was used as a decomposing agent. Therefore, the content of these substances was ND (1 ppm or less).

[0176] [Example 2] (Small particle size process) The water-absorbent resin precursor (1) obtained in Production Example 1 was further pulverized by a pin mill and classified by a JIS standard sieve with an opening of 106 μm to obtain an irregularly pulverized water-absorbent resin precursor (2). The mass average particle diameter of the water-absorbent resin precursor (2) was 50 μm.

[0177] 1800 parts by mass of 0.9% by mass sodium chloride aqueous solution (physiological saline) was added to 200 parts by mass of the obtained water absorbent resin precursor (2), and the mixture was left at room temperature for 8 hours or more to prepare a simulated used water absorbent resin (3). The gel particle size (mass average particle size when converted into a dry product) of the simulated used water absorbent resin (3) was 48 μm. Here, "the gel particle size of the water absorbent resin (simulated used water absorbent resin (2)) is 49 μm when converted into a dry product" means that the ratio of particles having a particle size of 48 μm or more and particles having a particle size of less than 48 μm is 50 mass% each among all particles (100 mass%) of the water absorbent resin. Therefore, for the simulated used water absorbent resin (3) obtained in Example 1, the ratio of particles having a particle size of 80 μm or less when converted into a dry product was more than 50 mass%, specifically, about 70 mass%.

[0178] (Solubilization process) A decomposition treatment was carried out in the same manner as in Comparative Example 1, except that 200.0 g of the above-mentioned simulated used water absorbent resin (3) was used instead of 200.0 g of the simulated used water absorbent resin (1) (solubilization step). The pH of the mixture in Example 2 was confirmed to be 8.0 to 8.5. In Comparative Example 1, it took 2 hours to solubilize the entire amount (almost 100%) of the simulated used water absorbent resin (1), but in Example 2, it took 1 hour to solubilize the entire amount of the simulated used water absorbent resin (3). This solubilized simulated used water absorbent resin (3) was used as the solubilized polymer (2).

[0179] The pH of the solubilized polymer (2) aqueous solution was measured with a pH meter and found to be 8.09. The solubilized polymer (2) aqueous solution had a solids concentration of 9.05% by mass, a YI value of 3.81, and a mass average particle diameter Mw of 221,000.

[0180] Next, as in Comparative Example 1, 16.2 g of a 15% by mass aqueous solution of sodium carbonate was added, and the mixture was stirred for 3 hours while maintaining the temperature at 25° C., thereby removing the decomposition agent (hydrogen peroxide) remaining in the aqueous solution. In addition, in the production process of the solubilized polymer (2), no transition metal (Fe, etc.) or L-ascorbic acid was used as a decomposition agent. Therefore, the content of these substances was ND (1 ppm or less).

[0181] [Table 1]

[0182] (result) Various decomposition conditions were shown in Examples 1-2 and Comparative Examples 1-5. Among them, Comparative Example 1 (decomposition temperature 80°C, decomposition time 2 hours, Mw 501,000) and Comparative Example 2 (decomposition temperature 100°C, decomposition time 1 hour, Mw 481,000) show more decomposition than Comparative Examples 3 and 4 where no decomposition occurred, but the molecular weight Mw of the solubilized polymer after decomposition is large and decomposability is poor. On the other hand, the results of Examples 1-2 show that a solubilization method with excellent decomposability can be provided in which the molecular weight Mw after decomposition is 214,000 to 221,000 despite the relatively short decomposition time of 1 hour by reducing the particle size of the target water absorbent resin to a specific particle size.

[0183] In Comparative Example 5, the decomposition agent was polymerized (1.33 g of 30 mass% aqueous hydrogen peroxide solution was changed to 3.34 g of L-ascorbic acid and 0.46 g of iron sulfate heptahydrate (total 3.8 g)). As a result, although the decomposition itself was possible in a decomposition time of 2 hours, the molecular weight Mw after decomposition was 85,000, which was an excessively low molecular weight, and further, the YI value was high at 89.7, and the colorability was also poor.

[0184] [Comparative Example 6] To a reaction vessel, 90.2 g of acrylic acid, 46.9 g of ion-exchanged water, 0.36 g of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, and 130.3 g of the aqueous solution of the solubilized polymer (C5) obtained in Comparative Example 5 above (solid content concentration 9.45% by mass) were added and stirred.

[0185] Next, the reaction vessel was immersed in an ice bath, and 75.33 g of an aqueous sodium hydroxide solution (solid content concentration: 48.5% by mass) was added little by little while stirring so that the liquid temperature in the vessel did not exceed 30° C. Thereafter, the liquid in the vessel was replaced with nitrogen gas for 30 minutes.

[0186] Next, the reaction vessel was immersed in a warm water bath at 50° C., and while stirring the liquid in the vessel, 0.167 g of sodium persulfate and 0.0007 g of L-ascorbic acid were added when the liquid temperature reached 30° C., and the polymerization reaction started about 10 minutes later. Thereafter, the polymerization reaction was continued while immersed in the warm water bath, and 60 minutes after the start of polymerization, the hydrogel (C6) was taken out.

[0187] The obtained hydrogel (C6) was crushed with a meat chopper having a die diameter of 7.5 mm, and then dried with hot air at 190°C for 20 minutes. The gel was then crushed with a vibration mill, and further classified with JIS standard sieves having openings of 850 μm and 150 μm to obtain an irregularly crushed water-absorbent resin precursor (C6). The mass average particle diameter of the water-absorbent resin precursor (C6) was 350 μm.

[0188] 100 parts by mass of the obtained water absorbent resin precursor (C6) was evenly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.0 part by mass of propylene glycol, and 3.0 parts by mass of deionized water, and the mixture was heated at 100° C. for 45 minutes.

[0189] After the heat treatment, the mixture was cooled and mixed evenly with an aqueous solution of 1 part by mass of deionized water and 0.01 part by mass of trisodium diethylenetriaminepentaacetate as an additive for surface crosslinking. After drying at 60°C for 1 hour, the mixture was classified using a JIS standard sieve with a mesh size of 710 μm to obtain hydrotalcite (product name: DHT-6, manufactured by Kyowa Chemical Industry Co., Ltd., Mg6Al2(OH) 16 The water-absorbent resin (C6) was obtained by uniformly mixing 0.3 parts by mass of CO3·4H2O and 0.5 μm volume average particle diameter. The physical properties of the obtained water-absorbent resin (C6) are shown in Table 2.

[0190] [Example 3] A water-absorbent resin (3) was obtained by the same procedure as in Comparative Example 6, except that the solubilized polymer (1) obtained in Example 1 was used instead of the comparative solubilized polymer (5) in Comparative Example 6. The physical properties of the obtained water-absorbent resin (3) are shown in Table 2.

[0191] [Example 4] A water absorbent resin (4) was obtained in the same manner as in Example 3, except that the surface crosslinking agent solution and the additives after surface crosslinking were changed.

[0192] Specifically, the surface crosslinking agent solution was changed to one consisting of 0.040 parts by mass of ethylene glycol diglycidyl ether, 2.45 parts by mass of propylene glycol, 3.55 parts by mass of deionized water, and 0.75 parts by mass of aluminum sulfate 14-18 hydrate, and the additive after surface crosslinking was changed to an aqueous solution consisting of 1 part by mass of deionized water, 0.03 part by mass of diethylenetriaminepentaacetate·trisodium (DTPA·3Na), and 0.1 part by mass of polyethylene glycol 600 (trade name: PEG-600, manufactured by Sanyo Chemical Industries, Ltd.). The physical properties of the obtained water absorbent resin (4) are shown in Table 2.

[0193] [Table 2]

[0194] (summary) Comparing the water absorbent resin of Comparative Example 6, which was prepared by changing only the solubilizing polymer, with the water absorbent resin of Example 3, it is found that the solubilized polymer (C5), which was decomposed using a large amount of decomposition agent, had a decomposition time of 2 hours (twice that of the solubilized polymer (1)), and decomposition proceeded excessively (reduced molecular weight) due to the influence of the excessive decomposition agent, and further, the colorability of the water absorbent resin made from the solubilized polymer (C5) as a raw material was also reduced, making it unsuitable as a raw material for water absorbent resins. [Industrial Applicability]

[0195] According to one aspect of the present invention, there is provided a method for solubilizing a water-absorbent resin, which can decompose the water-absorbent resin in a short time without using a large amount of a decomposing agent. The solubilized polymer obtained by the method can be suitably used for various applications, particularly as a raw material for recycled water-absorbent resin for sanitary products such as paper diapers, sanitary napkins, and adult incontinence products.

Claims

1. A solubilization step of solubilizing a water-absorbent resin recovered from used absorbent articles or waste generated in a manufacturing process of the water-absorbent resin to obtain a solubilized polymer; and a particle size reduction step of pulverizing the water-absorbent resin so that the mass average particle size, calculated as a dry product, is 20 to 160 μm and / or so that the mass ratio of a particle fraction having a particle size of 80 μm or less, calculated as a dry product, is 40 mass% or more.

2. The method for solubilizing a water-absorbent resin according to claim 1 , wherein a decomposing agent is added to the water-absorbent resin in the solubilizing step.

3. The method for solubilizing a water-absorbent resin according to claim 2, wherein the amount of the decomposition agent added is 0.001 to 1 part by mass with respect to 100 parts by mass of the water-absorbent resin.

4. The method for solubilizing a water-absorbent resin according to claim 2 , wherein the decomposing agent is an oxidizing agent.

5. The method for solubilizing a water-absorbent resin according to claim 1, wherein the water-absorbent resin is heated to 50 to 130° C. in the solubilization step.

6. The method for solubilizing a water-absorbent resin according to claim 1 , wherein the particle size reduction step is carried out before the solubilization step or simultaneously with the solubilization step.

7. 2. The method for solubilizing a water-absorbent resin according to claim 1, wherein the particle size reduction step reduces the particle size of the water-absorbent resin in a dry state.

8. The method for solubilizing a water-absorbent resin according to claim 1, wherein the solubilizing polymer has a mass average molecular weight of 100,000 to 450,000.

9. 2. The method for solubilizing a water-absorbent resin according to claim 1, wherein the solubilizing polymer has a YI value of 10.0 or less.

10. The method for solubilizing a water-absorbent resin according to claim 1, wherein the solid content concentration of the solubilizing polymer is 1 to 90 mass%.

11. The method for solubilizing a water-absorbent resin according to claim 1, wherein the water-absorbent resin is a water-absorbent resin recovered from a used absorbent article.

12. A method for producing a water-absorbent resin, comprising the steps of: producing a water-absorbent resin from a monomer constituting the water-absorbent resin as a raw material; and using a solubilized polymer obtained by the method for solubilizing a water-absorbent resin according to any one of claims 1 to 11 as a part of the raw material.

13. The method for producing a water-absorbing resin according to claim 12, comprising a step of preparing an aqueous monomer solution, a polymerization step, an optional gel crushing step, a drying step, an optional crushing step after drying, a classification step, and a surface crosslinking step, and the solubilizing polymer is added before the drying step.

Citation Information

Patent Citations

  • Recovery of pulp from water absorbable product

    JP1992317785A

  • Method for solubilizing water-swellable crosslinked polymer

    JP1993247221A

  • Method for decomposing water-absorbing polymer, method for producing recycle pulp, and water-absorbing polymer decomposer kit

    JP2019131789A

  • Degradation of superabsorbent polymers via oxidative degradation.

    JP2022544666A

  • Method for producing water-absorbing resin particles

    WO2020213298A1